Analysis Of Customer Relationship Management (Crm) On Customer Loyalty At PT Tower Agung West Sumatera - Supriadi, Toni; Ariska, Yesi Indian (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of Customer Relationship Management (CRM) on customer loyalty at PT Menara Agung in West Sumatra. The research method used is a quantitative approach with data collection techniques using direct telephone interviews with 100 customers who have interacted with the dealer CRM system to obtain direct information and assessments from customers. In an effort to measure the effect of Customer Relationship Management (CRM) on customer loyalty, data analysis was carried out using a simple linear regression method. The results of the study showed that CRM has a significant positive effect on customer loyalty, with a correlation coefficient of 0.654, this means that the correlation relationship between CRM and customer loyalty is in the strong category. In the determination correlation, the figure was 0.428 which means 42.8%, which means that customer loyalty is influenced by the effectiveness of CRM implementation. This study emphasizes the importance of an effective CRM strategy in increasing customer loyalty in the automotive industry, especially at PT Menara Agung, West Sumatra. The recommendation from this study is for PT Menara Agung to continue to strengthen and optimize its CRM strategy to maintain and increase customer loyalty.